Successful treatment with famciclovir for varicella zoster virus infection resistant to acyclovir. Issue 5 (May 2021) - Oka, Tomomi; Hishizawa, Masakatsu; Yamashita, Kouhei; Shiraki, Kimiyasu; Takaori-Kondo, Akifumi
Abstract: Varicella zoster virus (VZV) reactivates more frequently in immunocompromised patients than immunocompetent subjects and is a significant cause of morbidity and mortality. Acyclovir is frequently used for treatment against VZV reactivation. However, long-term use of acyclovir can result in the emergence of VZV strain resistant to acyclovir. Here, we report a 67-year-old man with adult T-cell leukemia who suffered from herpes zoster with acyclovir-resistant VZV after long-term prophylaxis. The isolated viruses from his skin lesions were a mixture of acyclovir-resistant and acyclovir-susceptible strains. Sequence analysis showed the presence of thymidine kinase (TK) mutations in the resistant clones. Interestingly, oral administration of famciclovir, a prodrug form of penciclovir, resulted in resolution of his herpes zoster, although most acyclovir-resistant strains of VZV were reported to be resistant to penciclovir. This implied that a certain amount of susceptible VZV with wild-type viral TK gene was present in vivo, and that famciclovir could be phosphorylated intracellularly by the intact viral kinases. As famciclovir is more potent and longer-acting than acyclovir, the susceptible strains might have suppressed the generation and proliferation of the resistant in vivo . Even when VZV is developing resistance to acyclovir, famciclovir might be effective at least in the early resistant phase.